2018
DOI: 10.1002/1873-3468.13122
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterisation of the HT3 motif of the polyhistidine triad protein D from Streptococcus pneumoniae

Abstract: The bacterium Streptococcus pneumoniae (the pneumococcus) is a major human pathogen that requires Zn for its survival and virulence in the host environment. Polyhistidine triad protein D (PhtD) has a known role in pneumococcal Zn homeostasis. However, the mechanistic basis of PhtD function remains unclear, partly due to a lack of structural information. Here, we determined the crystal structure of the fragment PhtD , containing the third Zn -binding histidine triad (HT) motif of the protein. Analysis of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…Although the Pht proteins have been refractory to high-resolution structure determination of the full-length protein, truncated domains containing individual HT motifs (HT1, HT2, and HT3) have been revealed (13,16,27). Structural analyses have suggested that each of the HT motifs of PhtD adopt a similar fold, with an equivalent capacity for Zn 2ϩ binding (13). Nonetheless, functional studies have shown that HT1 has the most critical role in zinc acquisition (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the Pht proteins have been refractory to high-resolution structure determination of the full-length protein, truncated domains containing individual HT motifs (HT1, HT2, and HT3) have been revealed (13,16,27). Structural analyses have suggested that each of the HT motifs of PhtD adopt a similar fold, with an equivalent capacity for Zn 2ϩ binding (13). Nonetheless, functional studies have shown that HT1 has the most critical role in zinc acquisition (15).…”
Section: Discussionmentioning
confidence: 99%
“…Here, the Pht proteins are shown to be cell wall-associated proteins that contribute to zinc acquisition via AdcAII, albeit with overlapping functionality (8,11,12). PhtD is the most highly conserved Pht family protein across pneumococcal strains and contains five HT motifs, with each motif predicted to bind zinc (13)(14)(15). Recent studies have shown that the HT1 motif, which is closest to the cell membrane, is the most important for the contribution of PhtD to zinc acquisition (15).…”
mentioning
confidence: 95%
“…terminal domain of polyhistidine triad protein D (PhtD-C) protein [13] and a P450 enzyme [unpublished].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…As an electron has a charge, there is a magnetic moment associated with the spin angular momentum: where e  is the Bohr magneton, Ŝ is the spin angular momentum, and the factor g can be obtained in accordance with Dirac's relativistic quantum mechanics. The free electron g-value is ge = 2.00231930436153 (53).…”
Section: Electron Spin and Spin Hamiltonianmentioning
confidence: 99%
“…Interestingly, AdcA-mediated Zn 2+ homeostasis does not show a significant dependency on the polyhistidine triad (Pht) proteins (from 90 to 116 kDa in size) [53], in contrast with AdcAII-mediated Zn 2+ homeostasis [54] where the proteins help to facilitate Zn 2+ acquisition. Pht proteins exist on the cell surface and are implicated in the Zn 2+ transport pathway but their role is poorly understood [53].…”
Section: Role Of Adca Zn 2+ -Binding Protein For S Pneumoniae Zn 2+mentioning
confidence: 99%